Ready and able? Professional awareness and responses to young carers in Switzerland. (July 2021) - Frech, Marianne; Wepf, Hannah; Nagl-Cupal, Martin; Becker, Saul; Leu, Agnes
Highlights: It is unknown how Swiss professionals support for young carers. Previous national research suggests a lack of support services for young carers. Professionals do provide individual as well as a family-centred support. Social services seem to be most inclined to initiating interdisciplinary support. Abstract: Background: The situation of children, adolescents, young adults with caring responsibilities and their families has only recently been addressed in the Swiss context. Initial findings show a low level of awareness among professionals towards young people with caring responsibilities, and also a lack of specific support services nationally for young carers. This might suggest that the support needs of young carers and young adult carers are not currently being recognised or met in Switzerland. Aim: The purpose of this analysis was to explore to what degree young carers' needs for support are currently met by professionals. We evaluated how professionals in Switzerland currently support young carers in their occupational context; what kind of organisations they refer young carers to; and if the current support approaches meet international recommendations (drawn from research and policy in other countries). Methods: Data from a cross-sectional online survey completed by 2142 professionals from education, healthcare and social services in Switzerland were analysed. The data included respondents' demographics, professional background, awareness of young carers' situations and circumstances, ability to support young carers, referrals to other organisations, as well as approaches to support young carers. We conducted text analysis of the open-ended answers according to Kuckartz (2014) as well as descriptive statistical analysis and Chi-Square independence tests. Results: Just over half (55.8%) of the professionals in our study reported being able to support young carers. Five different categories of support interventions were identified: counselling ; connecting with others ; emotional support ; including the family/network; and providing practical skills & illness-related knowledge . Professionals who reported that they themselves had a caring role when they were young were more likely to be able to support young carers ( p < .001 ). Professionals familiar with the term 'young carers' more often mentioned systemic support approaches (such as family-centred procedures and coordination/interdisciplinary cooperation) than those who were not familiar with the term. Conclusion: Study results show that many professionals in Switzerland address relevant realms and specific challenges for young people with caring responsibilities without being familiar with the experiences or needs of young carers. How they support young carers and young adult carers, perhaps surprisingly given their lack of awareness and specific knowledge, correspond with the main approaches currently found in the international literature recommendations for professionals working with young carers. The fact that systemic approaches of support were less often described, especially by professionals unfamiliar with the term 'young carer', raises the question whether appropriate sustainable and long-term support can be provided without having a clear understanding of the concept, experiences and specific needs of young carers. The study results provide a national starting point to develop support provisions and interventions for young carers. The results also offer relevant data for policy recommendations.